Avaliação da qualidade de vida relacionada à saúde por meio do questionário CHQ-PF50® em crianças com distúrbios da evacuação - Faleiros, Francisca Teresa Veneziano [UNESP] (Universidade Estadual Paulista (Unesp), 2005)
Neste estudo foi realizada a primeira avaliação da Qualidade de Vida Relacionada à Saúde em um grupo de 100 crianças com Distúrbios da Evacuação (Grupo Total-GT), classificadas de acordo com os Critérios de Roma II, divididas em: 57 com Constipação Intestinal Funcional (CIF), 29 com Retenção Fecal Funcional (RFF) e 14 com “Soiling“ Sem Retenção (SSR), homogêneas quanto às características demográficas. Utilizou-se o CHQ-PF50®, um instrumento genérico de medida de Qualidade de Vida Relacionada à Saúde, para se avaliar o impacto destes distúrbios na Qualidade de Vida dessas crianças, na percepção dos pais. Esse instrumento avalia o bem estar físico e psicossocial dos pacientes, por meio de 15 conceitos em saúde denominados Domínios, cada qual com uma escala de 0 a 100, com os maiores valores indicando melhor estado de saúde, bem estar e satisfação. Para a pontuação desse instrumento, obtém-se 2 escores agregados e sumários, o Escore Físico (PhS) e o Escore Psicossocial (PsS), através da transformação de 10 desses 15 Domínios. Os valores dos Escores Físico (PhS ) e Psicossocial (PsS ) das crianças do estudo comparados com aqueles das Populações de Referência: Normal e com Artrite Idiopática Juvenil, doença crônica com reconhecida repercussão da Qualidade de Vida, mostraram-se inferiores. Na comparação entre os diferentes subgrupos, obteve-se comprometimento somente do Escore Físico (PhS) entre Constipação Intestinal Funcional e “Soiling” Sem Retenção. No estudo de correlações entre os Escores Físico (PhS) e Psicossocial (PsS) com a Pontuação dos Distúrbios da Evacuação, correspondente à abordagem clínica e o Escore de Barr, correspondente à avaliação laboratorial, não houve correlação estatisticamente significante, mostrando...

In this study we assessed a serie of 100 pediatric patients aged from 5 to 12 years. They were diagnosed with Defecation Disorders and classified as to The Rome II criteria, being 57 with Functional Constipation (FC), 29 with Functional Fecal Retention (FFR) and 14 with Non-retentive Fecal Soiling (NRFS). Socio-demographic variables were comparable in all the groups. Besides routine clinical approach with imaging, we explored measures of health assessment by the Child Health Questionnaire-Parent Form-50 item - CHQ - PF50 ® - a valid health related quality of life tool. The CHQ- PF50 ® was considered for objective measure of parentþs perception of health status and overall well being of their children. This is a multidimensional tool composed by 15 health concepts (domains) scored from 0 to 100, with higher scores meaning better health status and well being. Additionally, two aggregated summary scores - a Physical (PhS) and Psychosocial (PSS) scores were calculated by factorial analysis, by using 10 of 15 health concepts. The individual scores and the aggregated PhS and PsS scores were compared to reference values in healthy and arthritic Brazilian children, being worse in the children with Defecation Disorders. Comparisons among the 3 groups with Defecation Disorders indicated significant difference for PhS scores, which were lower in NRFS compared to FC cases. The PhS and PsS were not correlated with the clinical and imaging scoring; this might point to independency or non redundancy of these measures for the clinical decision. In conclusion, these scores provided by a generic health related quality of life tool were considered useful for clinical assessment of Defecation Disorders in children. As reported for other diseases, parents-by-proxy self-reported health status tools can be considered as outcome measure for treatment decision guidance.
Keywords: Pediatria - Manuais, guias etc; Qualidade de vida - Avaliação; Evacuação - Distúrbios; Defecation disorders